(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article discusses the technology of automatically creating and combining vector layers of flood areas based on water level data and a digital terrain model in order to view flooded areas on a geographical map. Special attention is paid to the problems of forming polygons of flood areas from geographical points of flood areas. The program code for creating shape layers from the obtained polygons and combining several shape layers into one shape layer is given.